Meristem micropropagation of cassava (Manihot esculenta) evokes genome-wide changes in DNA methylation - Kitimu, Shedrack R.; Taylor, Julian; March, Timothy J.; Tairo, Fred; Wilkinson, Mike J.; Rodríguez López, Carlos M. (Frontiers in Plant Science, 2015)
There is great interest in the phenotypic, genetic and epigenetic changes associated with plant in vitro culture known as somaclonal variation. In vitro propagation systems that are based on the use of microcuttings or meristem cultures are considered analogous to clonal cuttings and so widely viewed to be largely free from such somaclonal effects. In this study, we surveyed for epigenetic changes during propagation by meristem culture and by field cuttings in five cassava (Manihot esculenta) cultivars. Principal Co-ordinate Analysis of profiles generated by Methylation Sensitive Amplified Polymorphism (MSAP) revealed clear divergence between samples taken from field-grown cuttings and those recovered from meristem culture. There was also good separation between the tissues of field samples but this effect was less distinct among the meristem culture materials. Application of methylation-sensitive Genotype By Sequencing (msGBS) identified 105 candidate epimarks that distinguish between field cutting and meristem culture samples. Cross referencing the sequences of these epimarks to the draft cassava genome revealed 102 sites associated with genes whose homologues have been implicated in a range of fundamental biological processes including cell differentiation, development, sugar metabolism, DNA methylation, stress response, photosynthesis, and transposon activation. We explore the relevance of these findings for the selection of micropropagation systems for use on this and other crops.